2021
DOI: 10.1371/journal.pone.0253628
|View full text |Cite
|
Sign up to set email alerts
|

Initial collection, characterization, and storage of tuatara (Sphenodon punctatus) sperm offers insight into their unique reproductive system

Abstract: Successful reproduction is critical to the persistence of at-risk species; however, reproductive characteristics are understudied in many wild species. New Zealand’s endemic tuatara (Sphenodon punctatus), the sole surviving member of the reptile order Rhynchocephalia, is restricted to 10% of its historic range. To complement ongoing conservation efforts, we collected and characterized mature sperm from male tuatara for the first time. Semen collected both during mating and from urine after courting contained m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Finally, of the 69 instances where a male successfully secured a mating opportunity, five appeared to be 'dry'. We define these as matings that were behaviourally typical, with courting being observed beforehand and an adequate amount of time for sperm deposition to have occurred elapsing before interruption (>5 min) (Lamar et al, 2021(Lamar et al, , 2023; however, no sperm or seminal fluid of any kind was present on the outside of or just inside either tuatara's cloacae. In all five of these instances the male shuddered shortly after mounting the female, a presumed indication of sperm ejaculation in this species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, of the 69 instances where a male successfully secured a mating opportunity, five appeared to be 'dry'. We define these as matings that were behaviourally typical, with courting being observed beforehand and an adequate amount of time for sperm deposition to have occurred elapsing before interruption (>5 min) (Lamar et al, 2021(Lamar et al, , 2023; however, no sperm or seminal fluid of any kind was present on the outside of or just inside either tuatara's cloacae. In all five of these instances the male shuddered shortly after mounting the female, a presumed indication of sperm ejaculation in this species.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we report that 11% of observed matings appeared dry. Three of the five observed dry mating events were observed from the start of mating, when the male mounted the female; in these instances, we can be sure that the pair was not prematurely interrupted (Lamar et al, 2021(Lamar et al, , 2023. Individuals were allowed to mate for between 5 and 10 min after discovery, and in all cases no seminal fluid was found on or in the cloacal opening of the female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note many sperm cryopreservation protocols developed to date have used sperm collected postmortem, due to the large quantities and quality of sperm obtained and the ease of protocol development this confers (Young et al 2017(Young et al , 2021(Young et al , 2022Campbell et al 2021aCampbell et al , 2021bSandfoss et al 2021). However, encouragingly, two recent studies have looked at sperm collected non-lethally, including the first study on tuatara (Lamar et al 2021;Hobbs et al 2022). We also believe that further studies on fundamental reptile reproductive ecology and physiology, along with testing fundamental hypotheses around cryopreserving reptile reproductive cells and tissues (Campbell et al 2021a) will aid with these conservation and research goals.…”
Section: Reptilesmentioning
confidence: 95%
“…Encouragingly, while the majority of ARTs studies to date have been focussed on squamates and the saltwater crocodile, a recent study reported the first collection, characterisation, and storage of tuatara (Sphenodon punctatus) sperm (Lamar et al 2021). Although preliminary, the authors reported low levels of live sperm recovery post-thaw using the commercial cryoprotectant Synth-a-Freeze™ (containing 10% DMSO buffered with HEPES), making it the first ART study for the ancient reptile order Rhynchocephalia (Lamar et al 2021). That means there has now been at least one published study on ARTs in all four of the extant reptile orders, a small but important step forward in reptile conservation.…”
Section: Reptilesmentioning
confidence: 99%